2022
DOI: 10.1111/hsc.13718
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and measuring the work‐related quality of life among those working in adult social care: A scoping review

Abstract: Adult social care in England "covers social work, personal care and practical support for adults with a physical disability, a learning disability, or physical or mental illness, as well as support for their carers" (p4, (National Audit Office, 2018)) and it has been experiencing many long-standing challenges, which have been exacerbated during the COVID-19 pandemic (Bottery, 2020). These include, for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 147 publications
1
12
0
2
Order By: Relevance
“…Drivers of OER under various contexts have remained a key research area for the last few years (Symitsi et al ., 2021). Researchers have used a variety of latent constructs, such as employee well-being (Silarova et al ., 2022), job satisfaction (Van Vu et al ., 2022), etc., to explain employee experience. In most cases, these studies have used survey-based methods for data collection using the Likert scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drivers of OER under various contexts have remained a key research area for the last few years (Symitsi et al ., 2021). Researchers have used a variety of latent constructs, such as employee well-being (Silarova et al ., 2022), job satisfaction (Van Vu et al ., 2022), etc., to explain employee experience. In most cases, these studies have used survey-based methods for data collection using the Likert scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scoping review [ 37 ] indicated an absence of agreement on a definition and measurement of CWRQoL in adult social care. As a result, there is limited evidence on how to improve CWRQoL among people working in adult social care.…”
Section: Resultsmentioning
confidence: 99%
“…For example, supervisor and manager support could be measured by (or a modified version of) the Organizational Stress Questionnaire (VOS-D) [ 41 ] and measuring tasks could start by adopting the Task and Job Analysis Tool [ 42 ], which was further developed for the LTC sector [ 38 ]. The findings of the scoping review identified different existing scales that have been used previously in the literature to measure various domains [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations